Hubungan Dukungan Orang Tua dan Sekolah terhadap Sexual Abstinence pada Remaja - Arum Setyanandini; Tanjung Anitasari Indah Kusumaningrum (Universitas Muhammadiyah Semarang, 2021)
Background: Reproductive health problems such as STI and HIV/AIDS, and Unwanted Pregnancy are vulnerable to be experienced by adolescents if they do not have the ability and confidence to perform sexual abstinence. Parents and schools are considered appropriate parties to provide support to adolescents to perform sexual abstinence. Objective: This study was to analyze the relationship between parental and school support for sexual abstinence in high school adolescents in Pugung District, Lampung Province. Methods: this type of research is analytic observational with a cross sectional approach. Sampling using Proportional Random Sampling technique, with a total sample of 130 respondents. The statistical test of this study used the Fisher exact test. Results: there is no relationship between parental support (p-value 0.672 > 0.05) and school (p-value 1,000 > 0.05) with sexual abstinence in high school adolescents in Pugung District. Conclusion: It is necessary to explore other appropriate sources of support for adolescents and to expand the scope of research for further research, both in urban and rural areas.